Mengasah Keterampilan Menyimak Bahasa Inggris melalui Video YouTube Bersubtitle dan Repetition Drill Interaktif untuk Anak-Anak Panti Asuhan Bonang Banjarmasin (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2026)
Listening skills are frequently regarded as the most challenging aspect of English language acquisition due to the complexity of the cognitive processes involved. In an orphanage environment, limited access to learning resources remains a primary obstacle to the development of this competence. This community outreach initiative aims to sharpen the listening skills of children at the Bonang Orphanage in Banjarmasin through the integration of subtitled YouTube videos and interactive repetition drill techniques. The implementation method involved 20 children selected via purposive sampling, utilizing a one-group pretest-posttest design. The intervention procedure encompassed the presentation of listening strategies, interactive discussions, and structured repetition exercises designed to build phonological automaticity. Quantitative evaluation results indicated a significant improvement, with the participants' mean score rising from 82.9 on the pretest to 86.7 on the posttest, with a maximum achievement score of 94. The discussion reveals that the use of subtitles serves as a visual scaffolding mechanism that facilitates sound-to-form mapping, while repetition drills strengthen the participants' working memory. Overall, the utilization of digital media and repetitive exercises proved effective in lowering cognitive barriers and increasing the participants' active engagement in English language learning.